Organoid intelligence for developmental neurotoxicity testing - Alam El Din, Dowlette-Mary; Shin, Jeongwon; Lysinger, Alexandra; Roos, Matthew J.; Johnson, Erik C.; Shafer, Timothy J.; Hartung, Thomas; Smirnova, Lena (Frontiers in Cellular Neuroscience, 2024)
The increasing prevalence of neurodevelopmental disorders has highlighted the need for improved testing methods to determine developmental neurotoxicity (DNT) hazard for thousands of chemicals. This paper proposes the integration of organoid intelligence (OI); leveraging brain organoids to study neuroplasticity in vitro, into the DNT testing paradigm. OI brings a new approach to measure the impacts of xenobiotics on plasticity mechanisms -a critical biological process that is not adequately covered in current DNT in vitro assays. Finally, the integration of artificial intelligence (AI) techniques will further facilitate the analysis of complex brain organoid data to study these plasticity mechanisms.The research described in this article has been reviewed by the Center for Computational Toxicology and Exposure, U.S. Environmental Protection Agency, and approved for publication. Approval does not signify that the contents necessarily reflect the views and policies of the Agency, nor does mention of trade names or commercial products constitute endorsement or recommendation for use.